The Future of the World Economy is an Integrated World Economic Structure - Glazyev, Sergey Yurievich; Ajvazov, Aleksandr Ervinovich; Belikov, Vladimir Aleksandrovich (Economy of Regions, 2018)
Global changes in the modern world cannot be adequately described on the basis of neoliberal thinking and require a new approach. It can be formed on the basis of the cyclical-wave characterization of the development of mankind. The hypothesis about the wave-like development of the world economy with a certain cyclicity lies at the heart of this research. The authors determined the economic basis of the formation, development and change of these waves (technological ways and technical revolutions). These changes reflect in the cyclical fluctuations of the world economy. The mechanism of these fluctuations is described by the theory of “large cycles of the economic conjuncture” by N. Kondratiev. The authors propose a methodology and methodological tools for analyzing and forecasting cyclic-wave processes in the economic development. The study has concluded that it is the regularities of K-cycles that allow one to correctly assess the ongoing processes in the world economy, to forecast possible variants of their development. The authors came to the conclusion that the development of the world economic structure is necessarily accompanied by a cyclical shift in the instruments of capital accumulation (material and financial expansion). These processes are reflected in the periodic replacement of scientific paradigms of economic development and management. The state always takes an active part in the phase of the dominance of productive capital, and the ideological paradigm is of a directing nature. While in the phase of domination of financial capital the liberal paradigm becomes dominant. We have substantiated the thesis about the transition from the American to the Asian systemic cycle of capital accumulation, which would inevitably lead in the middle of the 21st century to the shift of the center of the world economy from the West to the East. The paper concludes that the world is facing a change from the Monopolistic world economic structure to the Integrated world economic structure. The authors formulated the main contradiction of our present day - the confrontation of the dying Industrial Civilization in the face of the cumulative West and the emerging Information Society. The authors analyzed the main tendencies, problems and possible alternatives to the development of the world economy. It can ensure the development and adoption of political decisions for the most painless transition of Russia to the emerging forms and institutions of the global economy.